The Effect of Captivity on the Dynamics of Active Bacterial Communities Differs Between Two Deep-Sea Coral Species - Galand, Pierre E.; Chapron, Leila; Meistertzheim, Anne-Leila; Peru, Erwan; Lartaud, Franck (Frontiers in Microbiology, 2018)
Microbes play a crucial role in sustaining the coral holobiont's functions and in particular under the pressure of environmental stressors. The effect of a changing environment on coral health is now a major branch of research that relies heavily on aquarium experiments. However, the effect of captivity on the coral microbiome remains poorly known. Here we show that different cold-water corals species have different microbiome responses to captivity. For both the DNA and the RNA fraction, Madrepora oculata bacterial communities were maintained for at least 6 months of aquarium rearing, while Lophelia pertusa bacteria changed within a day. Interestingly, bacteria from the genus Endozoicomonas, a ubiquitous symbiont of numerous marine hosts, were resilient and remained active in M. oculata for several months. Our results demonstrate that a good knowledge of the coral microbiome and an understanding of the ecological strategy of the holobiont is needed before designing aquarium experiments.